Chronic Inflammation Might Protect Hemodialysis Patients From Severe COVID-19 - Prietl, Barbara; Odler, Balazs; Kirsch, Alexander H.; Artinger, Katharina; Eigner, Manfred; Schmaldienst, Sabine; Pfeifer, Verena; Stanzer, Stefanie; Eberl, Anita; Raml, Reingard; Pieber, Thomas; Rosenkranz, Alexander R.; et al. (Frontiers in Immunology, 2022)
Background: Hemodialysis patients (HD) are expected to have excess mortality in coronavirus disease 2019 (COVID-19). This was challenged by a recent study reporting HD patients to have comparable mortality and less ICU admissions when hospitalized with COVID-19. An altered immune system due to chronic inflammation might protect HD-patients from severe COVID-19. Therefore, we aimed to describe the peripheral blood immune phenotype in HD-patients and respective controls with COVID-19. Methods: Sixty-four patients (31 HD, 33 non-HD) with PCR-confirmed COVID-19 and 16 control patients (10 HD, 6 non-HD) were prospectively included. According to symptoms, COVID-19 patients were categorized as asymptomatic/mild, moderate or severe COVID-19 phenotypes. Cytokine profiling and immune phenotyping was performed. Results: Th1 and Th17 plasma cytokine levels were highly increased in HD patients without COVID-19 and were not significantly regulated during COVID-19. In non-HD COVID-19 patients these cytokines increased significantly with disease severity. While all patients with moderate or severe COVID-19 showed hallmarks of COVID-19 such as decreased CD3+, CD4+ and CD8+ and CD4+CD25hiFoxP3+ regulatory T cells, significantly increased CD38+CD8+ effector memory and CD38+CD8+ TEMRA T cells were detected in moderate/severe COVID-19 HD patients, which was not observed in non-HD patients with moderate or severe COVID-19. Furthermore, CD161+CD8+ T cells decreased significantly in non-HD COVID-19 patients dependent on disease severity, but not in HD patients. Dynamics of B cells and subtypes were comparable in HD and non-HD COVID-19 patients. Conclusions: HD patients might be protected from severe COVID-19 due to their chronic inflammatory state with increased CD38+CD8+ effector memory and TEMRA T cells as well as CD161+CD8+ T cells.